Design for additive manufacturing: Trends, opportunities, considerations, and constraints - Thompson, Mary Kathryn; Moroni, Giovanni; Vaneker, Tom; Fadel, Georges; Campbell, R. Ian; Gibson, Ian; Bernard, Alain; Schulz, Joachim; Graf, Patricia; Ahuja, Bhrigu; Martina, Filomeno (Elsevier, 2016)
The past few decades have seen substantial growth in Additive Manufacturing (AM) technologies. However, this growth has mainly been process-driven. The evolution of engineering design to take advantage of the possibilities afforded by AM and to manage the constraints associated with the technology has lagged behind. This paper presents the major opportunities, constraints, and economic considerations for Design for Additive Manufacturing. It explores issues related to design and redesign for direct and indirect AM production. It also highlights key industrial applications, outlines future challenges, and identifies promising directions for research and the exploitation of AM's full potential in industry.
Keywords: Design; Manufacturing; Additive Manufacturing